Etnik Nusantara Modern Terminal Bus Tipe A Cijulang Pangandaran - Muflihul Iman; Maulana Dian P; Egga Ryandona (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
ABSTRACT West Java is one of the regions in Indonesia with a variety of extraordinary tourist destinations. The attraction of destinations in West Java can invite local and international tourists to come to visit. Pangandaran is one of the regencies in West Java Province. The area of Pangandaran Regency is 168,509 hectares, with the greatest potential of Pangandaran Regency is tourism both beach and river attractions. Seeing the number of tourist attractions in Pangandaran Regency, the number of tourists reached 3.6 million tourist visits to tourist attractions in Pangandaran. The large number of private vehicle users that cause congestion is caused by inadequate infrastructure facilities in Pangandaran Regency such as public transportation, namely bus transportation. Currently, the terminal facilities owned by the Pangandaran Regency government only have 3 terminals with the condition of the bus terminal is very worrying, not managed properly, does not facilitate to existing tourist areas, and there are no terminal facilities that function to serve intercity transportation between provinces (AKAP). Therefore, Cijulang Pangandaran Type A Bus Terminal presents a Modern Ethnic Nusantara concept to introduce and preserve the Ethnic Nusantara in West Java. Keywords : Bus Terminal, Cijulang Pangandaran, Ethnic Nusantara Modern